Work Motivation As A Determinant Of Employee Loyalty And Retention In The Industrial Sector - Reis Alta Peggi; Zhivastya Zhiakhira; Shelva Aurellia Naswya; Gita Purnama Sari (Jurnal Bisnis dan Manajemen (JURBISMAN), 2025)
With the rapid growth of Indonesian industry, businesses must remain productive and have competent and loyal human resources. Work motivation is a key component that influences employee retention, loyalty, and performance in this industry. Motivated employees demonstrate the highest levels of dedication and performance, which benefits the company. A literature review method was used in this study to investigate the relationship between work motivation and employee loyalty and retention in the industry. The results show that effective motivation management can increase employee commitment by up to 30%, reduce turnover rates, and help companies compete in the global market. Sustainable motivation stems from internal components, such as psychological needs, and external components, such as leadership style, communication, rewards, and career development. Therefore, it is crucial to use holistic motivation strategies to create a productive, stable, and conducive work environment.